Antibiotic Resistance in Developing Countries: Emerging Threats and Policy Responses - Hedayatullah Ehsan (Public Health Challenges)
Abstract Objectives This narrative review investigates the key drivers of antimicrobial resistance (AMR) in low‐ and middle‐income countries (LMICs) and evaluates the effectiveness of policy responses. It highlights the unique challenges these regions face and provides actionable recommendations for mitigating AMR. Methods A comprehensive literature search was conducted across PubMed, Scopus, and Web of Science, supplemented by reports from global health organizations. Studies published between 2010 and 2023 focusing on AMR in LMICs were included. Thematic analysis synthesized data into key drivers, policy challenges, and intervention strategies. Results The major drivers of AMR in LMICs include unregulated antibiotic sales, overuse and misuse of antibiotics, weak healthcare infrastructure, poor infection control, and environmental contamination. Socio‐economic factors, such as self‐medication and limited healthcare access, exacerbate the problem. Although strategies like antimicrobial stewardship (AMS) programs, regulatory reforms, and public education campaigns have shown potential, their effectiveness is hindered by resource limitations and governance challenges. Conclusions Combatting AMR in LMICs requires tailored, multi‐sectoral interventions that strengthen healthcare systems, enforce strict regulations, enhance public awareness, and foster international collaboration. Policymakers must prioritize investments in diagnostic infrastructure, AMS, and culturally adapted public health campaigns to reduce resistance and safeguard global health.